The quartet [compact disc, unabridged] : orchestrating the second American Revolution, 1783-1789 - Ellis, Joseph J. (Books on Tape ; Random House Audio, 2015)
The unexpected story of why the thirteen colonies, having just fought off the imposition of a distant centralized governing power, would decide to subordinate themselves anew.